Power distance on employee performance in agro-based small-medium enterprises (SME) in Sabaragamuwa province - Thilakshana, U.P.G.K.J.; Koralagama, D.N.; Sandika, A. (Colombo : Sri Lanka Association for the Advancement of Science, 2021)
Organizational culture directly influences employee performance and labor productivity. Geert Hofstede evaluated the organizational culture over four dimensions; namely, power distance (PD), uncertainty avoidance (UAD), individualism (IDV), and masculinity (MAS) by assigning equal weights to each component in generating the indices. Power distance influences employee performance, labor productivity and profitability of a firm. Hofstede (1984), identified power distance as the extent to which the members of a society accept that power in institutions and organizations is distributed unequally. Despite Sri Lanka having an estimated power distance index (PDI) of 80, adequate research has not been carried out on agro-based industries. Thus, this study attempts to calculate the PDI of four agro-based SME categories including dairy, tea, plant production (ornamental plants, timber plants), and agro-input supply. Quantitative data were collected by administering a questionnaire survey (n=60) with operational-level employees adopting simple random sampling technique. The Northouse leadership questionnaire was used to assess the leadership styles. Variables of consultation by superiors, respectability for superiors, conflicting relationship with superiors, and interactions with superiors were used to calculate PDI. All variables were quantified using a five points Likert scale. Democratic leadership was profound in all four categories due to harmoniousness within employees and their leaders in enterprises. Thus, a moderate power distance (PDI dairy= 67.71; PDI tea=49.52; PDI plant= 65.21, and PDI agro-input= 49.24) was resulted. Although Hofstede identified Sri Lanka as a high-power distance (80) country in the year 2011, the calculated value for the agro-based industry (57.92) indicated moderate power distance. It indicates better human relationships within agro-based enterprises and their productivity. It is necessary to improve the two-way communication channel between employees and leaders, provide better guidance to employees to reduce power distance and thereby improve the performance level.
Keywords: Agro-Industry; Employee Performance; Hofstede Dimensions; Leadership Styles; Power Distance Index